Assessment of burnout, resilience, and thriving among academic health professionals: findings from an international study - Nahas, Abdul Rahman Fata; Elnaem, Mohamed Hassan; Mubarak, Naeem; Khatwa, Merna Abou; Barakat, Muna; Faller, Erwin; Kassem, Lamyaa M.; Ramatillah, Diana Laila; Jaber, Ammar; Akkawi, Muhammad Eid; Al-Shami, Abdulkareem Mohammed; Chandran, Sarath; et al. (Frontiers in Public Health, 2024)
Introduction Burnout, resilience, and thriving significantly impact academics, particularly in health professions, where responsibilities are extensive. This study aimed to explore these constructs among academic health professionals, examining sociodemographic and work-related factors influencing these outcomes. Methods A cross-sectional study was conducted among academic health professionals via web-based professional networks from August 2022 to February 2023. Validated tools were used, and descriptive and inferential statistics were applied. Results 505 participants were included, predominantly female (63%), with a mean age of 38.15 ± 9.6 years. High burnout was reported by 10.9%, 13.7% experienced exhaustion, and 6.3% were disengaged. Resilience and thriving were moderate at 59.2 and 51.9%, respectively. Age correlated negatively with burnout (r = −0.131, p = 0.003) but positively with resilience (r = 0.178, p < 0.001). Females reported higher exhaustion (p = 0.014), while males showed greater resilience (p = 0.016). Instructors exhibited lower resilience compared to assistant professors (p < 0.001) and associate professors (p < 0.001). Those at public universities reported higher exhaustion than those at private universities (p < 0.001). Conclusion Variable levels of burnout, resilience, and thriving were observed among academic health professionals, influenced by sociodemographic and work-related factors. Interventions targeting resilience and thriving may mitigate burnout risk and enhance engagement among academics in health professions.